Unique nest architecture in the North African osmiine bee Hoplitis (Hoplitis) mucida (Hymenoptera, Megachilidae) - Andreas Müller; Volker Mauss; Rainer Prosi (Journal of Hymenoptera Research, 2017)
The osmiine bee species Hoplitis mucida is considered to consist of two subspecies with H. mucida mucida (Dours, 1873) ranging from northwestern Africa to Israel and Jordan and H. mucida stecki (Frey-Gessner, 1908) occurring in southwestern Europe and Sicily. The discovery of nests of H. mucida in Morocco and Tunisia revealed striking differences in the nesting biology of the two subspecies. In North Africa, females construct fully exposed, cake-like nests of mud on the flat surface of rocks and stones containing 8–12 vertically oriented brood cells, rendering these nests unique among osmiine bees regarding both nesting site and nest architecture. In contrast, in Europe females build their few-celled mud nests inside small rock cavities. This discrepancy in the nesting biology is paralleled by considerable morphological differences between the two subspecies suggestive of a long geographical isolation. Due to these biological and morphological differences, we propose to elevate the European subspecies H. mucida stecki to species rank.